Is Davao City, Philippines Ready For E-Health? - F. Sumaylo, Dennis John; C. Salas, Christian Joy (2015)
In the Philippines wherein most concepts are taken from a western perspective, the transmission of information from the source to the receiver rely solely on what is affordable and logistically doable resulting to areas in Geographically Isolated and Disadvantaged Area (GIDA) sites to receive less or no health care information from the government.